NORMAL FORMS OF THE FORMAL DIFFERENTIAL EQUATIONS - Benazic Tomé, Renato Mario (2004)
In this paper, we resolve the problem of finding a formal change of coordinates between formal vector field and another more simple (its «canonical form»}. In particular, we proof the Poincaré's theorem of formal linearization and the Poincaré-Dulac theorem.